EXPERT SYSTEM WITH FUZZY MANDANI FOR PREDICTION OF DIGESTIVE DISEASES - Eli Safitri; Nurmayanti Nurmayanti (IJISCS (International Journal of Information System and Computer Science), 2023)
Digestive diseases of the stomach often occur in everyday life. So that almost everyone experiences the disease. every day the health center is full of patients who experience digestive disorders in the stomach. Not only medical treatment but also consultation regarding solutions for digestive ailments, especially in the stomach. Every day the health center records and reports the number of visiting patients, but consulting in this service is considered ineffective, so it takes quite a long time. To facilitate and speed up services at the puskesmas, an expert system was created to assist the puskesmas and patients in conducting consultation services the puskesmas. An expert system is a system that seeks to produce a decision that is equal to that of an expert or expert using a computer system so that the decision results are accurate. The expert system is implemented using the fuzzy Mamdani method so that it can assist in determining a diagnosis with the maximum. The results of this study are 6 types of digestive diseases in the stomach, using the Mamdani fuzzy expert system. So that it produces an accurate diagnosis. In making the web program, it has been tested using Black Box testing.